Análise morfológica superficial e resistência de união do selamento dentinário imediato submetido a diferentes tratamentos para remoção de cimento temporário - Maciel, Carolina Menezes (2014)
The objective of this study was to analyze the surface morphology of the Immediate Dentin Sealing (IDS) and its bond resistance after subjecting it to different treatments for removal of the temporary luting agent. Fifty-five caries-free human third molars had their occlusal enamel removed and the dentin was ground with a 600-grit sandpaper until standardization of the smear layer. IDS was performed with a three-step conventional adhesive (Adper Scothbond Multipurpose, 3M/ESPE). Temporary restorations were fixed over the sealed dentin with eugenol-free temporary luting agent (RelyX Temp NE, 3M/ESPE). The specimens were stored in 100% humidity for 7 days at 37ºC. After this period, the specimens were split into 5 groups (n=11), according to the type of treatment applied in the removal of the residual temporary luting agent: control group (CG), treatment with hand scaler (TS), treatment with hand scaler + sodium bicarbonate jet (BJT), treatment with hand scaler + aluminum oxide jet (AJT) and treatment with hand scaler + diamond bur (DBT). After treatment, nine specimens from each group received a new adhesive layer followed by restoration with composite resin. Forty-eight hours after storage, the specimens were sectioned in sticks of approximately 0.49 mm2 and subjected to fracture in an Instron (0.5 mm/min) universal testing machine. The microtensile bond strength values were subjected to ANOVA (one factor) complemented by Turkey’s test (p < 0.05). The fractures were visualized with a stereomicroscope magnification glass. They were classified as interfacial, mixed and cohesive (in resin and dentin). In order to analyze the surface morphology of the immediate dentin sealing the two remaining specimens of each group were examined under scanning electron microscopy. The mean values of microtensile bond strength in MPa and the respective standard deviations were: CG - 33.74 (6.3); TS - 29.04 (6.4); BJT - 39.93 (4.9); AJT - 32.53 (7.4); DBT - 35.93 (7.5). Statistical differences were observed only among groups BJTa and TSb (p=0,018). The resulting fractures were found to be interfacial (76.5%), mixed (11%), cohesive in resin (9.4%) and cohesive in dentin (3.1%). All treatments succeeded in causing modifications in the hybrid layer surface. Based on the applied methodology, it can be concluded that none of the treatments influenced bond strength significantly when compared to the control group. The predominant fracture after mechanical testing was interfacial. A significant difference was observed only between groups TS and BJT. The treatments induced different alterations on the surface of the immediate dentin sealing.